Administration of a PTEN inhibitor BPV(pic) attenuates early brain injury via modulating AMPA receptor subunits after subarachnoid hemorrhage in rats. (19th February 2015) - Chen, Yujie; Luo, Chunxia; Zhao, Mingyue; Li, Qiang; Hu, Rong; Zhang, John H.; Liu, Zhi; Feng, Hua
Highlights: We explored the effect of PTEN inhibitor BPV(pic) on rats subjected to subarachnoid hemorrhage. BPV(pic) significantly improved neurological deficits, reduced neural cell death. BPV(pic) significantly alleviated brain edema and BBB disruption. BPV(pic) inhibited PTEN expression and phosphoinositide 3-phosphatase activation of PTEN. BPV(pic) regulated AMPA receptor subunits expression. Abstract: The aim of this study was to investigate whether the phosphatase and tensin homolog deleted on chromosome ten (PTEN) inhibitor dipotassium bisperoxo(pyridine-2-carboxyl) oxovanadate (BPV(pic)) attenuates early brain injury by modulating α-amino-3-hydroxy-5-methyl-4-isoxa-zolep-propionate (AMPA) receptor subunits after subarachnoid hemorrhage (SAH). A standard intravascular perforation model was used to produce the experimental SAH in Sprague–Dawley rats. BPV(pic) treatment (0.2 mg/kg) was evaluated for effects on neurological score, brain water content, Evans blue extravasation, hippocampal neuronal death and AMPA receptor subunits alterations after SAH. We found that BPV(pic) is effective in attenuating BBB disruption, lowering edema, reducing hippocampal neural death and improving neurological outcomes. In addition, the AMPA receptor subunit GluR1 protein expression at cytomembrane was downregulated, whereas the expression of GluR2 and GluR3 was upregulated after BPV(pic) treatment. Our results suggest that PTEN inhibited by BPV(pic) plays a neuroprotective role in SAH pathophysiology, possibly by alterations in glutamate AMPA receptor subunits.